SWOT ANALYSIS AS FORMULATION OF MARKETING STRATEGIES ON NOUGGY CULINARY BUSINESS IN MALANG CITY - Tri Utami, Lia Ujung; Evelina, Tri Yulistyawati (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This research aims to formulate effective marketing strategies for the "NOUGGY" culinary business in Malang using SWOT analysis. A qualitative method with a descriptive approach was employed, utilizing in- depth interviews with the business owner, employees, suppliers, competitors, and consumers to gather data. The study analyzed internal factors (strengths and weaknesses) and external factors (opportunities and threats) affecting the business. Key findings indicate that "NOUGGY" benefits from unique raw materials and strong supplier relationships, but faces challenges such as inconsistent product quality and limited market reach. The analysis identified opportunities in untapped market segments and threats from rising competitors. The research provides theoretical insights for improving marketing strategies and practical recommendations for collaboration with stakeholders. The novelty of this study lies in its detailed application of SWOT analysis to a local SME in the culinary sector.